Birds of a Feather Flock Together: Extent of Long-Term Consistency of Colony-Size Choice in Cliff Swallows - Brown, Charles R.; Hannebaum, Stacey L. (Frontiers in Ecology and Evolution, 2022)
Explaining why animal groups vary in size is a fundamental problem in behavioral ecology. One hypothesis is that life-history differences among individuals lead to sorting of phenotypes into groups of different sizes where each individual does best. This hypothesis predicts that individuals should be relatively consistent in their use of particular group sizes across time. Little is known about whether animals’ choice of group size is repeatable across their lives, especially in long-lived species. We studied consistency in choice of breeding-colony size in colonially nesting cliff swallows (Petrochelidon pyrrhonota) in western Nebraska, USA, over a 32-year period, following 6296 birds for at least 4 breeding seasons. Formal repeatability of size choice for the population was about 0.41. About 45% of individuals were relatively consistent in choice of colony size, while about 40% varied widely in the colony size they occupied. Birds using the smaller and larger colonies appeared more consistent in size use than birds occupying more intermediate sized colonies. Consistency in colony size was also influenced by whether a bird used the same physical colony site each year and whether the site had been fumigated to remove ectoparasites. The difference between the final and initial colony sizes for an individual, a measure of the net change in its colony size over its life, did not significantly depart from 0 for the dataset as a whole. However, different year-cohorts did show significant net change in colony size, both positive and negative, that may have reflected fluctuating selection on colony size among years based on climatic conditions. The results support phenotypic sorting as an explanation for group size variation, although cliff swallows also likely use past experience at a given site and the extent of ectoparasitism to select breeding colonies.